Malignant cell-specific pro-tumorigenic role of type I interferon receptor in breast cancers. Issue 7 (2nd July 2020) - Odnokoz, Olena; Yu, Pengfei; Peck, Amy R.; Sun, Yunguang; Kovatich, Albert J.; Hooke, Jeffrey A.; Hu, Hai; Mitchell, Edith P.; Rui, Hallgeir; Fuchs, Serge Y.
ABSTRACT: Within the microenvironment of solid tumors, stress associated with deficit of nutrients and oxygen as well as tumor-derived factors triggers the phosphorylation-dependent degradation of the IFNAR1 chain of type I interferon (IFN1) receptor and ensuing suppression of the IFN1 pathway. Here we sought to examine the importance of these events in malignant mammary cells. Expression of non-degradable IFNAR1 S526A mutant in mouse mammary adenocarcinoma cells stimulated the IFN1 pathway yet did not affect growth of these cells in vitro or ability to form subcutaneous tumors in the syngeneic mice. Remarkably, these cells exhibited a notably accelerated growth when transplanted orthotopically into mammary glands. Importantly, in human patients with either ER+ or ER- breast cancers, high levels of IFNAR1 were associated with poor prognosis. We discuss the putative mechanisms underlying the pro-tumorigenic role of IFNAR1 in malignant breast cells.